Take-off analysis of the Olympic ski jumping competition (HS-106 m) - Virmavirta, M.; Isolehto, J.; Komi, P.; Schwameder, H.; Pigozzi, F.; Massazza, G. (Journal of Biomechanics, 2009)
The take-off phase (approximately 6 m) of the jumps of all athletes participating in the individual HS-106 m hill ski jumping competition at the Torino Olympics was filmed with two high-speed cameras. The high altitude of the Pragelato ski jumping venue (1600 m) and slight tail wind in the final jumping round were expected to affect the results of this competition. The most significant correlation with the length of the jump was found in the in-run velocity (r=0.628, p<0.001, n=50). This was a surprise in Olympic level ski jumping, and suggests that good jumpers simply had smaller friction between their skis and the in-run tracks and/or the aerodynamic quality of their in-run position was better. Angular velocity of the hip joint of the best jumpers was also correlated with jumping distance (r=0.651, p<0.05, n=10). The best jumpers in this competition exhibited very different take-off techniques, but still they jumped approximately the same distance. This certainly improves the interests in ski jumping among athletes and spectators. The comparison between the take-off techniques of the best jumpers showed that even though the more marked upper body movement creates higher air resistance, it does not necessarily result in shorter jumping distance if the exposure time to high air resistance is not too long. A comparison between the first and second round jumps of the same jumpers showed that the final results in this competition were at least partly affected by the wind conditions.